Design of scaled down model of a tower crane mast by using similitude theory - Kenan, Hamit; Azeloglu, Oktay (ELSEVIER SCI LTD, 2020)
In this study, a tower crane mast which is very sensitive to the dynamic effects that will occur due to its delicate structure was scaled by similitude theory for the purpose of using in experimental studies. The variables that describe the structure in terms of dynamic were determined and pi groups were created by using the Buckingham Pi Theorem. A finite element model that is able to calculate the natural frequencies, mass parti-cipation factors, and draw the mode shapes of a structure composed of space frame elements was developed. The mast was scaled down to use in the laboratory environment with two different scale factors as 30 and 40. The most suitable model which represents the dynamic behavior of the real-size tower crane mast for the experi-mental studies was determined by comparing the modal analysis results of the real-size and scale models.
Keywords: Similitude theory; Tower crane; Scale model; Modal analysis; Finite element model; DYNAMIC-BEHAVIOR; MOTION; Engineering